The Path to Self-Management: A Qualitative Study Involving Older People with Multiple Sclerosis - Ploughman, Michelle (University of Toronto Press Incorporated, 2012)
Purpose: This qualitative study sought to explore older people's experience of ageing with multiple sclerosis (MS) and to describe the natural history of self-management from their points of view. Methods: Eighteen people over age 55 and living with MS for at least 20 years were recruited from an MS clinic and rehabilitation outpatient records. Interviews (60–80 min), using open-ended questions, explored participants' lifelong experiences of MS. Following interview transcription, data were coded and analyzed; themes, subthemes, and their relationships were described based on consensus. Results: Participants recounted their diagnosis process, their life experience with MS, and how they eventually accepted their disease, adapted, and moved toward self-management. The findings included vivid descriptions of social relationships, health care interactions, overcoming barriers, and the emotions associated with living with MS. A conceptual model of phases of self-management, from diagnosis to integration of MS into a sense of self, was developed. Conclusions: Study participants valued self-management and described its phases, facilitators, and inhibitors from their points of view. Over years and decades, learning from life experiences, trial and error, and interactions with health care professionals, participants seemed to consolidate MS into their sense of self. Self-determination, social support, strong problem-solving abilities, and collaborative relationships with health professionals aided adaptation and coping. Findings from this study make initial steps toward understanding how MS self-management evolves over the life course and how self-management programmes can help people with MS begin to manage wellness earlier in their lives.